**Q) **Find the value of m for which the quadratic equation (m + 1) y^{2} – 6(m+1) y + 3(m+9) = 0, m ≠ -1 has equal roots. Hence find the roots of the equation.

**Ans: **Given quadratic equation is: (m + 1) y^{2} – 6(m+1) y + 3(m+9) = 0

If we compare to ax^{2} +bx + c = 0, then we can see that

a = (m+1),

b = – 6 (m+1)

and c = 3 (m+9)

For a quadratic equation to have real (positive) and equal roots, the discriminant D should be 0.

or b^{2} – 4ac = 0

Substituting the values of a, b and c, we get:

∴ (- 6(m+1))^{2} – 4(m+1) x 3(m+9) = 0

∴ 36(m+1)^{2} – 12(m+1)(m+9) = 0

∴ 3(m^{2}+ 2m + 1) – (m^{2} +10m + 9) = 0

∴ 3m^{2}+ 6m + 3 – m^{2} -10m – 9 = 0

∴ 2m^{2} -4m – 6 = 0

∴ m^{2} – 2m – 3 = 0

∴ (m – 3)(m + 1) = 0

m = 3, m = -1

Since m ≠ -1, Hence, m = 3.

**Therefore, for m = 3, the given quadratic equation will have equal roots**

* Please press “like” button if you liked the solution. *

**Check:*** **Let’s put the value m = 3 in the given quadratic equation and check if we get 2 equal roots:*

*(m + 1) y ^{2} – 6(m+1) y + 3(m+9) = 0*

*∴ (3+1)y ^{2}*– 6 (3 +1)y + 3(3 + 9) = 0

*∴ 4 y ^{2}*– 24 y + 36 = 0

* ∴ y ^{2}*– 6 y + 9 = 0

*∴ (y -3) ^{2}* = 0

*It gives two equal roots of y = 3. Hence, our answer m = 3 is correct.*

* Please press “like” button if you liked the solution.*